2001
DOI: 10.1115/1.1374201
|View full text |Cite
|
Sign up to set email alerts
|

An in Vitro Model of Neural Trauma: Device Characterization and Calcium Response to Mechanical Stretch

Abstract: An in vitro model for neural trauma was characterized and validated. The model is based on a novel device that is capable of applying high strain rate, homogeneous, and equibiaxial deformation to neural cells in culture. The deformation waveform is fully arbitrary and controlled via closed-loop feedback. Intracellular calcium ([Ca2+]i) alterations were recorded in real time throughout the imposed strain with an epifluorescent microscopy system. Peak change in [Ca2+]i recovery of [Ca2+]i and percent responding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 26 publications
2
72
0
Order By: Relevance
“…Nonetheless, the relative alterations in cell viability following the loading regimes used in this study are consistent with those following both in vivo and in vitro models of neural trauma (Gennarelli et al, 1982;Ellis et al, 1995;Meaney et al, 1995;Ahmed et al, 2000). Strain rate-dependent responses to mechanical loading have previously been reported for neural cells (Ellis et al, 1995;Cargill and Thibault, 1996;LaPlaca et al, 1997;Geddes and Cargill, 2001;LaPlaca et al, 2005), but this is the first report of such a response in neural co-cultures based on 3-D biomechanical inputs.…”
Section: Discussionsupporting
confidence: 63%
“…Nonetheless, the relative alterations in cell viability following the loading regimes used in this study are consistent with those following both in vivo and in vitro models of neural trauma (Gennarelli et al, 1982;Ellis et al, 1995;Meaney et al, 1995;Ahmed et al, 2000). Strain rate-dependent responses to mechanical loading have previously been reported for neural cells (Ellis et al, 1995;Cargill and Thibault, 1996;LaPlaca et al, 1997;Geddes and Cargill, 2001;LaPlaca et al, 2005), but this is the first report of such a response in neural co-cultures based on 3-D biomechanical inputs.…”
Section: Discussionsupporting
confidence: 63%
“…To accurately model the progression of damage, the constitutive model should be extended to account for the time-dependent behavior of brain tissue. Finally, the injury criterion was based on the stretch of neural axons; however, it has been shown that neural damage is also dependent on the rate of loading (Elkin and Morrison III 2007;Geddes and Cargill 2001;LaPlaca et al 2005). Therefore, in future studies, the effect of strain rate on the functional damage of neural cells should be incorporated into a measure of injury.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been numerous experimental studies aimed at defining injury thresholds for the functional damage of neural cells (Bain and Meaney 2000;Elkin and Morrison III 2007;Geddes and Cargill 2001;Morrison et al 2003;Wolf et al 2001). These injury thresholds are measures of stress or strain at either the cellular or tissue level.…”
Section: Axonal Strain Injury Criterionmentioning
confidence: 99%
“…Using lactate dehydrogenase (LDH) release or highmolecular-weight tracer uptake to evaluate membrane damage in various TBI models, our laboratory and others have established that membrane disruption can occur at the moment of injury, suggesting that the traumatic event evokes direct mechanical poration of the neuronal cell membrane (Pettus et al, 1994;LaPlaca et al, 1997;Geddes and Cargill, 2001;Geddes et al, 2003;Singleton and Povlishock, 2004). In these studies, it was suggested that the altered neuronal membrane permeability generated ionic disturbances to precipitate cell death.…”
Section: Membrane Disruption and Enduring Membrane Permeabilitymentioning
confidence: 99%